The Effect of Meta-Cognitive Therapy and Educating the Components of Spiritual Intelligence on Generalized Anxiety Disorder of Students - Ahmad Souri; Shahnam Azadmard; Omid Zahedi; Jamal Ashoori (Iranian Association of Health Education and Health Promotion, 2016)
Background and objective: Meta-cognitive therapy and educating components of spiritual intelligence were two important methods in treating anxiety disorders. This study was aimed to investigate the effect of meta-cognitive therapy and educating  components of spiritual intelligence in decreasing the symptoms of generalized anxiety disorder among students. Materials and methods:  This was a quasi-experimental study with a pre-test and post-test design. The statistical population included all students with generalized anxiety disorder that referred to counseling centers of Islamic Azad University, Mashhad branch in the year 2013. Totally 45 students were selected through available sampling method and randomly assigned to three groups. The experimental groups were educated for ten 70-minute sessions by meta-cognitive therapy and components of spiritual intelligence; the control group did not receive any treatment. For collecting data all groups completed the Cattell generalized anxiety questionnaire as a pre-test and a post-test. Data were analyzed with SPSS 19 and by univariate analysis of covariance (UNCOVA). Results: Both methods of meta-cognitive therapy and educating component of spiritual intelligence significantly led to the decrease of generalized anxiety disorder symptoms of students. Also, the findings showed there wasn't any significant differences between meta-cognitive therapy and education component of spiritual intelligence methods in decreasing the symptoms of generalized anxiety disorder of students. Conclusion: Meta-cognitive therapy and educating the component of spiritual intelligence methods were equally effective in decreasing the generalized anxiety disorder of students. Therefore, counselors and therapists can use the mentioned methods in treating generalized anxiety of students. Paper Type: Research Article.